DESIGNING A PCR TEST SYSTEM FOR THE GENETIC DIAGNOSIS OF RICKETTSIOSES - Yessimseit , D.T.; Abdeliyev , B.Z.; Kassenova , A.K.; Abdirassilova , A.A.; Turebekov , N.A.; Zhumadilova , Z.B.; Kovaleva , G.G.; Tokmurziyeva , G.Zh.; Ryabushko , E.A.; Umarova , S.K.; Rysbekova , A.K. (Eurasian Journal of Applied Biotechnology, 2024)
To ensure the biological safety of the country, it is necessary to develop priority areas of biotechnology, create advanced means of detecting pathogenic biological agents. Rickettsia bacteria, one of the most widespread zoonotic pathogens worldwide, continues to be a serious problem for public health. One of the solutions to the problems related to the situation of the effectiveness of rickettsiosis monitoring is the widespread introduction into clinical practice of modern diagnostic methods based on nucleic acid amplification (MANC) methods, in particular PCR. The paper presents the test results of experimental series of rickettsia detection kits. Purpose. Development and construction of experimental series of PCR test systems for the detection of rickettsioses, conducting control tests to work out optimal conditions in order to achieve maximum sensitivity and specificity of the drug.